(untitled) (Annals of Medical Research, 2022)
Aim: Depression and suicide are more common comorbidities in end-stage renal disease patients than in healthy populations, but suicide has rarely been studied. Our research aimed to evaluate the relation between depressive mood and suicidal ideation in hemodialysis cases. Materials and Methods: 112 hemodialysis patients were included in the study. The sociodemographic characteristics of the patients and the laboratory test results were obtained from the file records. Beck Depression Inventory (BDI) and Suicidal Ideation Scale (SIS) were administered through face-to-face interviews. Results: We enrolled 112 volunteer hemodialysis patients [female/male, 48/64; age 59.9±13.5 years; hemodialysis duration 36.5 months (6-291)]. We divided the cases into two groups based on their BDI scores as those with depressive mood (BDI score ≥ 17, n= 47) (42%) and those without (BDI score < 17, n= 65) (58%). Of the cases with depression, 38 (68.1%) were female, and 15 were male (31.9%)( p<0.001). While age, calcium, and SIS were higher in the depressive group than in the other group, serum albumin levels were lower. A positive correlation was found between BDI and SIS (r=0.216, p<0.05). ​The suicide ideation scale was positively correlated with age (r=0.254, p<0.001), BDI (r=0.231, p<0.05), and hemoglobin level (r=0.194, p<0.05), while it was negatively correlated with serum albumin level (r= -0.250, p<0.001). In Multiple Logistic Regression analysis, gender (OR: 5.915, 95%CI [2.086-16.776], p<0.001) and serum albumin level (OR: 0.021, 95%CI [0.003-0.149], p<0.001) were determined as independent risk factors for depressive mood. However, in Multiple Logistic Regression analysis, there was no significant relationship between SIS score and depressive mood (OR: 1.070, 95%CI [0.937-1.221], p˃0.05). Conclusion; Depression was higher in hemodialysis patients, and depressed patients had higher suicidal ideation. Depression had no increment effect on the suicide risk. We think it would be beneficial to consider suicidal ideation along with depression.